Escalation and De-Escalation of Commitment to Information Technology Projects: Insights from an Approach-Avoidance Punctuated Equilibrium Model - PAN, Gary (Institutional Knowledge at Singapore Management University, 2005)
This paper outlines a project evaluation model for examining escalation and de-escalation of commitment to information systems projects. We view escalation and de-escalation of commitment as processes involving recurring instances of approach-avoidance conflict. In the model, the sequential mapping of project events is integrated with a model of approach-avoidance conflict that identifies periods of gradual evolution at two separate levels of social analysis (project and work) that are punctuated by sudden, revolutionary periods of rapid change. By conceiving the processes of commitment escalation and de-escalation as sequences of events involving approach-avoidance conflicts, researchers may develop a deeper understanding of how and why projects escalate and de-escalate. Practitioners can also utilize the evaluation model in the analyses of projects that have faced escalation to diagnose the issues surrounding the escalation and devise useful de-escalation strategies for future project development. The evaluation model is developed and illustrated with a case study that exhibits both project escalation and de-escalation conditions.